(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article explores the most commonly used programs for creating web applications and discusses their types and implications. It provides an overview of key programming languages such as HTML/CSS, JavaScript, PHP, Python, Ruby, Java, and .NET, highlighting their roles in web development. The article also examines front-end and back-end frameworks that enhance web application development and discusses the importance of considering project requirements, scalability needs, and developer expertise when selecting programs. By understanding the landscape of web application development programs, developers can make informed decisions to build robust and user-friendly web applications.